Determination of the s‐phase formation coefficient of plasma nitrided austenitic steel. Issue 2 (4th November 2020) - Reinders, P.M.; Patel, R.R.; Musekamp, J.; Kaestner, P.; Hoche, H.; Bräuer, G.; Oechsner, M.
Abstract: Plasma nitriding is an effective surface hardening treatment for austenitic stainless steels. During plasma nitriding, s‐phase formation takes place which is not only responsible for high hardness and wear resistance but also for good corrosion resistance. In order to estimate the thickness of the s‐phase for austenitic stainless steel in a plasma nitriding process, an empirical model is devised. A number of plasma nitriding processes of austenitic stainless steel (304 L) were carried out with varying treatment temperature from 360 °C to 450 °C and process duration ranging from 10 hours to 24 hours with constant pressure, voltage, pulse‐to‐pause‐ratio and gas mixture. A time‐temperature dependent s‐phase formation coefficient is determined by measuring the thickness of the s‐phase using a scanning electron microscope (SEM) and glow discharge optical emission spectroscopy (GDOES). The developed model is verified by three controlled experiments. This model fits the thickness of the s‐phase with an error of less than 6 %. Abstract : A model for determining the s‐phase thickness for plasma nitriding of the austenitic steel 1.4307 was developed. The model allows to determine the thickness of the s‐phase before plasma nitriding depending on the process temperature and duration. Translation abstract: Das Plasmanitrieren ist ein wirksames Verfahren zur Randschichthärtung von austenitischen Stählen. Während des Plasmanitrierens bildet sich die s‐Phase, welche für eine hohe Härte, Verschleißfestigkeit und Korrosionsbeständigkeit verantwortlich ist. Um die Dicke der s‐Phase eines austenitischen Stahls, welche sich während des Plasmanitrierens einstellt, im Vorfeld abschätzen zu können, wird ein empirisches Modell aufgestellt. Dazu werden verschiedene Plasmanitrierprozesse durchgeführt, die in der Behandlungstemperatur von 360 °C bis 450 °C und in der Behandlungsdauer von 10 Stunden bis 24 Stunden variiert werden. Andere Prozessparameter wie Druck, Spannung, Puls‐Pause‐Verhältnis oder Gaszusammensetzung bleiben konstant. Als Untersuchungswerkstoff dient der austenitische Stahl 1.4307. Ein abhängiger s‐Phasen‐Bildungskoeffizient wird durch das Messen der s‐Phasendicken unter Verwendung eines Rasterelektronenmikroskops (REM) und die Glimmentladungsspektroskopie (GDOES) bestimmt. Das entwickelte Modell wird durch Kontrollversuche unter selben obengenannten Bedingungen überprüft. Das Modell erlaubt die Abschätzung der s‐Phasendicke mit einem Fehler von 6 %.